2017
DOI: 10.1016/j.biopsych.2016.12.021
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-Mediated Rescue of Fear Extinction Memory by miR-144-3p in Extinction-Impaired Mice

Abstract: These findings identify a fundamental role of miR-144-3p in the rescue of impaired fear extinction and suggest this miRNA as a viable target in developing novel treatments for posttraumatic stress disorder and related disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 55 publications
2
40
0
Order By: Relevance
“…It is now widely accepted that NOTCH transcription and translation is negatively regulated by microRNAs, which consequently affects the intensity of NOTCH signaling (Dias et al, ). This is in line with Murphy et al () who showed that impaired fear extinction, as frequently observed in PTSD patients, could be rescued by targeting genes in plasticity‐associated signaling cascades (i.e., NOTCH) to increase microRNA‐controlled gene expression in the amygdala. However, their findings are based on brain tissue, and future research is needed to determine whether similar effects can be found in humans and in peripheral tissues (e.g., blood).…”
Section: Discussionsupporting
confidence: 88%
“…It is now widely accepted that NOTCH transcription and translation is negatively regulated by microRNAs, which consequently affects the intensity of NOTCH signaling (Dias et al, ). This is in line with Murphy et al () who showed that impaired fear extinction, as frequently observed in PTSD patients, could be rescued by targeting genes in plasticity‐associated signaling cascades (i.e., NOTCH) to increase microRNA‐controlled gene expression in the amygdala. However, their findings are based on brain tissue, and future research is needed to determine whether similar effects can be found in humans and in peripheral tissues (e.g., blood).…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, aberrant miR-144 expression is associated with the pathogenesis of psychiatric disorders. In fear extinction-impaired animals, over expression of miR-144 in the amygdala can successfully rescue fear extinction memory by targeting Pten, Notch1 and Spred1, a group of genes important for the control of fear extinction [100], highlighting the significance of miR-144 for the memory-related activities.…”
Section: Function Of Mir-144/451 In Additional Tissuesmentioning
confidence: 99%
“…Most work examining behavioural effects of amygdalar miRNA focuses on fear learning (Volk et al ., ). For example, inhibiting miR‐34a in the basolateral amygdala inhibits cued fear learning by disinhibiting Notch1 signalling (Dias et al ., ), although overexpressing amygdalar miR‐144‐3p (which also targets Notch1) enhances fear extinction (Murphy et al ., ). While a picture of the role of amygdalar miRNAs in mediating behavioural changes in response to environmental stimuli (i.e.…”
Section: Introductionmentioning
confidence: 97%